Remifentanil and Nitrous Oxide Anesthesia Produces a Unique Pattern of EEG Activity During Loss and Recovery of Response - Eagleman, Sarah L.; Drover, Caitlin M.; Drover, David R.; Ouellette, Nicholas T.; MacIver, M. Bruce (Frontiers in Human Neuroscience, 2018)
Nitrous oxide (N2O) and remifentanil (remi) are used along with other anesthetic and adjuvant agents for routine surgical anesthesia, yet the electroencephalogram (EEG) changes produced by this combination are poorly described. N2O administered alone produces EEG spectral characteristics that are distinct from most hypnotics. Furthermore, EEG frequency-derived trends before and after clinically relevant time points vary depending on N2O concentration. Remifentanil typically increases low frequency and decreases high frequency activity in the EEG, but how it influences N2O’s EEG effect is not known. Previous attempts to characterize EEG signals of patients anesthetized with nitrous oxide using frequency-derived measures have shown conflicts and inconsistencies. Thus, in addition to determining the spectral characteristics of this unique combination, we also test whether a newly proposed characterization of time-delayed embeddings of the EEG signal tracks loss and recovery of consciousness significantly at clinically relevant time points. We retrospectively investigated the effects of remi and N2O on EEG signals recorded from 32 surgical patients receiving anesthesia for elective abdominal surgeries. Remifentanil and nitrous oxide (66%) were co-administered during the procedures. Patients were tested for loss and recovery of response to verbal stimuli after induction and upon cessation of anesthesia, respectively. We found that the addition of remifentanil to nitrous oxide anesthesia improves the ability of traditional frequency-derived measures, including the Bispectral Index (BIS), to discriminate between loss and recovery of response. Finally, we found that a novel analysis of EEG using nonlinear dynamics showed more significant differences between states than most spectral measures.